Aesthetics as a fundamental teaching discourse in the current Literacy (Tabanque. Revista Pedagógica, 2020)
The Word ‘Literacy’ has widen its concept frontiers in the last decades, especially due to the boom of the new technologies of the information and communication, which made necessary an educational system which includes these new forms of communication. This work is not a theoretical revision of the term itself, but it presents an analysis of the didactics principles for these disciplines: language-literature and visual thinking. It must be based on the demand of the social and cultural development of the current contexts. These disciplines perform their functions in the everyday life and communication situations, so the teaching-learning process of these languages must arise from the real communication situations and using these situations as the materials to analyze and get the competences on the visual and linguistic literacy. These are the requirements for the development of the critical thinking in order to be able to operate on the social and cultural progress in an appropriate, sensible and correct form.
Keywords: aesthetics; communication; image; interaction; language; literacy; literature; teaching training